The Emerging Roles of Endocrine Hormones in Different Arthritic Disorders - Bertoldo, Eugenia; Adami, Giovanni; Rossini, Maurizio; Giollo, Alessandro; Orsolini, Giovanni; Viapiana, Ombretta; Gatti, Davide; Fassio, Angelo (Frontiers in Endocrinology, 2021)
The relationship between hormones and the spectrum of rheumatic conditions has long been discussed in the literature, focusing primarily on sex hormones. In the last years, the interest in the crosstalk between hormones acting on the bone tissue (i.e. parathyroid hormone), modulators of the Wnt pathway (i.e. Dickkopf-1), and the immune system has grown. Osteoimmunology is the field of research that studies these connections. The purpose of this review is to discuss and summarize the role of bone-related hormones and cytokines in the main rheumatic disorders. We will describe this relationship from a biochemical, diagnostic and therapeutic perspective, with a particular focus on rheumatoid arthritis (RA), psoriatic arthritis (PsA) and ankylosing spondylitis (AS).